Error Bounds of Conjugate of a Periodic Signal by Almost Generalized Nörlund Means : Vishnu Narayan Mishra, Vaishali Sonavane - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we determine the error bounds of conjugate signals between input periodic signals and processed output signals, whenever signals belong to Lip(alpha, r)-class and as a processor we have taken almost generalized Nörlund means using head bounded variation sequences and rest bounded variation sequences. The results obtained in this paper further extend several known results on linear operators.